2021
DOI: 10.4082/kjfm.20.0025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physiotherapy Approaches in Low Back Pain: A Randomized Controlled Trial

Abstract: Background: The purpose of this study was to compare the effectiveness of rehabilitation approaches in individuals with low back pain (LBP) on pain, spinal mobility, disability, and muscular strength. Methods: Ninety volunteers were included and divided into four groups depending on the rehabilitation approach. Group 1, soft tissue mobilization techniques and stabilization exercises (n=24; 11 females (F), 13 males (M); group 2, Kinesio Taping and stabilization exercises (n=24; 12F, 12M); group 3, stabilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The key to using KT to relieve pain is how to choose the appropriate location, adjust the appropriate tension and determine the time of adhesive. Senbursa’s study found that KT was very effective in improving low back pain in a short period, and could immediately show pain relief during activity and relaxation without other adverse reactions [ 46 ]. However, some studies have found that the KT can significantly improve the pain, range of motion, and injury of patients with low back pain in the short term, and maintain the improvement of range of motion and injury in the long term, but there is no long-term effect on the improvement of pain [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The key to using KT to relieve pain is how to choose the appropriate location, adjust the appropriate tension and determine the time of adhesive. Senbursa’s study found that KT was very effective in improving low back pain in a short period, and could immediately show pain relief during activity and relaxation without other adverse reactions [ 46 ]. However, some studies have found that the KT can significantly improve the pain, range of motion, and injury of patients with low back pain in the short term, and maintain the improvement of range of motion and injury in the long term, but there is no long-term effect on the improvement of pain [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The key to using KT to relieve pain is how to choose the appropriate location, adjust the appropriate tension and determine the time of adhesive. Senbursa's study found that KT was very effective in improving low back pain in a short period, and could immediately show pain relief during activity and relaxation without other adverse reactions [44]. However, some studies have found that the KT can signi cantly improve the pain, range of motion, and injury of patients with low back pain in the short term, and maintain the improvement of range of motion and injury in the long term, but there is no long-term effect on the improvement of pain [45].…”
Section: Discussionmentioning
confidence: 99%
“…Allocation concealment was adequately reported by Added et al, [12] except in 11 studies where the concealment of allocation from the investigators was unclear (unclear risk of bias). [13][14][15][16][17][18][19][20][21][22][23] All of 12 trials failed to blind both the therapists and participants. [12][13][14][15][16][17][18][19][20][21][22][23] Among trials included in this review, all trials described clear inclusion and exclusion criteria.…”
Section: Methodologic Quality Assessmentmentioning
confidence: 99%
“…Adequate random sequence generation was reported in 10 trials. [12,[14][15][16][17][18][19][20]22,23] The outcome assessors were blinded in only 3 studies. [12,16,17] Trial registration number or study protocol was available for 1 trial.…”
Section: Methodologic Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation